The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/4165839
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Aerobic Exercise on Liver Tissue in Rats with NAFLD

Abstract: Objective. To observe the improvement effect of aerobic exercise on liver tissue of rats with NAFLD, explore whether it can reduce NAFLD symptoms without drug dependence, and provide certain data support for the relief of NAFLD by aerobic exercise. Methods. 40 healthful male SD rats have been divided into ordinary diet and high-fat diet. To observe whether the molding is forming after 6 weeks, then divide the rats into control (C), model (M), and exercise (E) group. E group received 8-week aerobic exercise int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…In the NAFLD progression, hepatic steatosis is the initial factor, and inflammatory response and oxidative stress are closely associated with insulin resistance as the pathological and physiological basis of the NAFLD progression. Owing to genetic susceptibility, obesity, overweight, and other causes, the body produces insulin resistance, resulting in liver steatosis, and excessive accumulation of free fatty acid in the liver causes lipotoxicity, leading to the damage of liver cells by endoplasmic reticulum stress and oxidative stress until apoptosis (18). In the present work, the NAFLD rat model was developed by feeding rats an HFD for eight weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the NAFLD progression, hepatic steatosis is the initial factor, and inflammatory response and oxidative stress are closely associated with insulin resistance as the pathological and physiological basis of the NAFLD progression. Owing to genetic susceptibility, obesity, overweight, and other causes, the body produces insulin resistance, resulting in liver steatosis, and excessive accumulation of free fatty acid in the liver causes lipotoxicity, leading to the damage of liver cells by endoplasmic reticulum stress and oxidative stress until apoptosis (18). In the present work, the NAFLD rat model was developed by feeding rats an HFD for eight weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the people in the world with NAFLD account for over 1:4 of the total population (18). Currently, due to the lack of detailed information about the underlying mechanisms of this disease, no definitive drug exists to treat NAFLD (19).…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%